2017
DOI: 10.1016/j.jiph.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to non-adherence with treatment among TB patients in Sodo Woreda, Gurage Zone, Southern Ethiopia: A qualitative study

Abstract: Poor adherence by tuberculosis (TB) patients to their medication contributes not only to the worsening of their TB situation but also paves a way for incidence of drug resistance. This study, hence, aims to explore factors contributing for non-adherence of TB treatment among TB patients in Sodo Woreda, Gurage Zone, Southern Ethiopia. A qualitative study, which included 22 in-depth interviews from four health centers and seven health posts, was conducted from February 25 to April 27, 2014. Although the drugs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
2
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 16 publications
7
59
2
10
Order By: Relevance
“…Poor patient-provider relationship also had significant association. This agreed to findings of studies in Sodo woreda, Southern Ethiopia [ 23 ]. Besides, alcohol intake had significant association with non-adherence.…”
Section: Discussionsupporting
confidence: 92%
“…Poor patient-provider relationship also had significant association. This agreed to findings of studies in Sodo woreda, Southern Ethiopia [ 23 ]. Besides, alcohol intake had significant association with non-adherence.…”
Section: Discussionsupporting
confidence: 92%
“…The barriers of poor adherance to DOT was due to patients not willing to come to the clinic for DOT on daily basis due to long distance, financial crisis for traveling (cost for transportation and accomodation) and lack of support from family and friends. Similar barrier factors for DOT were reported in other studies like in Nepal [21], Brazil [17], Ethiopia [22,23]. In addition, lack of awareness of TB and its consequences, and the belief, prompted many respondents to visit traditional healers [21].…”
Section: Discussionsupporting
confidence: 62%
“…Another study found that DOT can improve TB treatment adherence and protect TB patients from adverse outcomes by 25% [17]. Poor adherence by TB patients to their medication contributes not only to the worsening of their TB situation but also paves a way for the incidence of drug resistance [23].…”
Section: Discussionmentioning
confidence: 99%
“…Established referral procedures and feedback mechanisms between home-based care and the health care system [13] are necessary aspects of PHC reforms. Studies conducted on treatment adherence show that a good healthcare worker-patient relationship can contribute to better treatment adherence [3234]. Furthermore, literature shows that patients provided with adequate knowledge about treatment show high adherence rates as patient behaviour is largely influenced by knowledge and acceptance of their disease and treatment [33,34].…”
Section: Discussionmentioning
confidence: 99%